Investigating the prevalence of work-related musculoskeletal disorders among ICU nurses in the Sultanate of Oman - Abdelrahim, Rasha Ali; Nasser Al Hadhrami, Sumaiya; Ali Said Al Ghafri , Waria (International Journal of Occupational Safety and Health, 2026)
Introduction: Intensive Care Unit (ICU) nurses are increasingly exposed to work-related Musculoskeletal Disorders (MSD), making them among the most vulnerable healthcare workers globally. This study aims to investigate the prevalence of MSD among ICU nurses in Oman. It further examines the relationship between nursing activities and the prevalence of MSD among ICU nurses.Methods: This study deployed a cross-sectional research design and a concurrent observational ergonomic assessment. A Nordic Musculoskeletal Questionnaire was completed by a random sample of 171 nurses to assess their perception of MSD pain. Subsequently, 48 nurses were observed using the Rapid Upper Limb Assessment (RULA) tool to evaluate the impact of various nursing activities on nurses’ MSD. Results: The findings reveal a high prevalence of MSD symptoms among ICU female nurses. Significant associations were identified between adherence to safe work procedures and shoulder (p = 0.014), low back (p = 0.037), and foot/ankle pain (p = 0.022). Moreover, adults (heart Center) ICU were found to have the highest RULA score of about (6.6), followed by adults main, and pediatrics heart center (6.4) and (6.2) respectively.Conclusion: This study highlights the prevalence of Musculoskeletal Disorders among ICU nurses. It underscores the need for healthcare organizations to strengthen ergonomic training, patient-handling strategies, and workplace safety measures to support nurses’, safety, health, well-being and improve overall healthcare performance. The integration of occupational health and safety practices into ICU work environments enables policymakers, safety practitioners, and regulators to promote safety among ICU nurses.